Empowerment of coastal communities in Pante Paku Village, Bireuen District through the formation of tourism awareness groups (pokdarwis) in turtle and coral reef conservation activities [Pemberdayaan masyarakat pesisir pantai di Gampong Pante Paku Kabupaten Bireuen melalui pembentukan kelompok sadar wisata (pokdarwis) dalam kegiatan konservasi penyu dan terumbu karang] - Erlangga, E; Hasibuan, Anggi Agung Hamonangan; Muliani, M; Azis, M. Raziq; Abdi, M. Farhan; Akbar, Maulana; Maulana, Rahmatullah Rafi; Mahlil, M; Monica, Diffya; Fahrunnisyah, Nur Indah; Pratiwi, Riska Deviyani; Mila, Apryza; Jelita, J (Universitas Syiah Kuala, 2025)
The degradation of coral reefs and threats to turtle populations due to anthropogenic activities in Pante Paku Village, Jangka Sub-District, Bireuen District, have prompted the implementation of a community-based marine ecosystem conservation program. This program aims to conserve coral reefs and protect turtles through a participatory approach. A qualitative descriptive method was adopted, involving initial surveys, program socialization, community training, and ecosystem monitoring. The implementation of these activities coincided with the Student Organization Capacity Building Program (PPK Ormawa). The establishment of a Tourism Awareness Group (POKDARWIS) was also carried out within this program, making it a key strategy in increasing community participation in the sustainable management of coastal resources. Training activities focused on coral reef conservation through transplantation methods using rafts or concrete substrates, and turtle habitat protection through beach cleaning and the construction of semi-natural hatcheries. Monitoring activities, conducted from August to October 2024, used the Line Intercept Transect (LIT) method to evaluate coral reef conditions and collect turtle population data. The results of the program implementation indicate that this approach is effective in increasing public literacy and awareness regarding the importance of maintaining the sustainability of marine ecosystems. In conclusion, this program not only contributes to the preservation of marine biodiversity but also strengthens the socio-economic aspects of coastal communities through the sustainable utilization of resources.